1971
DOI: 10.1098/rspb.1971.0103
|View full text |Cite
|
Sign up to set email alerts
|

How penicillin kills bacteria: progress and problems

Abstract: Penicillins and cephalosporins are specific inhibitors of the biosynthesis of bacterial cell walls. This discovery was first made in 1957 and was based on two observations. First, penicillins induced the formation of protoplasts or spheroplasts in bacteria (organisms in which the cell wall has been lost or weakened) (Lederberg 1957). Secondly, a uridine nucleotide accumulated in Staphylococcus aureus and other bacteria inhibited by penicillin which had a striking relationship to the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 2 publications
(2 reference statements)
1
21
0
Order By: Relevance
“…Although it has been suggested (2,(6)(7)(8) that the effects of f,-lactam antibiotics on cell division, elongation, and shape are due to the presence of distinct penicillin-sensitive enzymes specifically involved in peptidoglycan metabolism for these three processes, little evidence has been produced to substantiate this view. Multiple penicillin-sensitive enzymes (7,9,10) and penicillin binding proteins (8,9,11) with different sensitivities to fl-lactam antibiotics are present in E. coli, and recently we have shown that one of the six penicillin binding proteins (protein 2) is specifically involved in the maintenance of the rod shape of E. coli (8).…”
mentioning
confidence: 87%
“…Although it has been suggested (2,(6)(7)(8) that the effects of f,-lactam antibiotics on cell division, elongation, and shape are due to the presence of distinct penicillin-sensitive enzymes specifically involved in peptidoglycan metabolism for these three processes, little evidence has been produced to substantiate this view. Multiple penicillin-sensitive enzymes (7,9,10) and penicillin binding proteins (8,9,11) with different sensitivities to fl-lactam antibiotics are present in E. coli, and recently we have shown that one of the six penicillin binding proteins (protein 2) is specifically involved in the maintenance of the rod shape of E. coli (8).…”
mentioning
confidence: 87%
“…The peptidoglycan isolated from cell walls of this organism (12,18) is similar to that of penicillin-susceptible organisms (10,23,25). In a previous paper (27) it was reported that the membrane fraction derived from P. aeruginosa KM 338 catalyzes peptidoglycan synthesis, including the cross-linking reaction.…”
mentioning
confidence: 97%
“…3751 membranes to which radioactive penicillin had been bound revealed multiple peaks of radioactivity. Prior treatment with cephalothin abolished some but not all of the bands (19,20 …”
Section: Introductionmentioning
confidence: 99%
“…3751 membranes to which radioactive penicillin had been bound revealed multiple peaks of radioactivity. Prior treatment with cephalothin abolished some but not all of the bands (19,20 (23) and that, under these conditions, the activity of the inactivated D-alanine carboxypeptidase of B. subtilis is restored (17). (26); the sample application buffer customarily included 3% 2-mercaptoethanol.…”
mentioning
confidence: 99%